THE 15-MINUTE CITY AND SOCIAL BEHAVIOR CHANGES IN THE TOD AREA: BLOK M-SISINGAMANGARAJA TOD CASE STUDY - Julfikar, Dede; Yola, Lin (UI Scholars Hub, 2025)
The changing process of the city can be due to economic development that results in urbanization then enlarges the city. This situation affects the growth and evolution of other activities in urban areas such as the emergence of new residential areas, industrial zones, and trade and service (commercial) areas. The government of DKI Jakarta is targetting to develop many public transportation infrastructure due to its target of 2040 70% of Jakarta residents live near by transit points. So that the distance of residential residents to urban facilities can be reached within 15 minutes of walking, cycling or using public transportation. This study method is based on literature searches and stakeholder interviews by looking at comparisons of other city developments and DKI Jakarta Government policies related to Transit-Oriented Development areas which are part of the realization of 15-Minute City. The Jakarta 15-Minute City development concept is the government's effort to create an inclusive environment that is a place for all parts of its citizens and an effort to maintain sustainable development in SDG-11.